Guidelines to the agroecology-I context document - Masso, Cargele; Lamanna, Christine; Kettle, Christopher J.; Wickramaratne, Chaturangi; Jones, Sarah K.; Dickens, Chris (International Water Management Institute, 2022)
The purpose of the Context Document is threefold: first, to characterize the environmental, social and economic context of each Agroecological Living Lab (ALL); second, to understand the data and information currently available in each ALL; and third to characterize how and the extent to which agroecological principles are already being employed in each ALL. The Context Document is not meant to be a quantitative baseline or an exhaustive report, but rather a broad overview of the situation in each ALL. The data collected during the Context Document can be utilized during the visioning and assessment phases and is fundamental to describe the situation in each ALL and will inform the impact assessment. It will also be valuable to all other WPs as it will provide foundational data for their investigation.